Performance analysis of a NOMA-VLC system with random user location - Prakriti Saxena; Yeon Ho Chung (ICT Express, 2023)
In this paper, we investigate the performance of a downlink non-orthogonal multiple access (NOMA) based visible light communication (VLC) system. We consider that the users are randomly located following a binary Poisson point (BPP) Process. The performance of the considered system is evaluated by deriving novel closed-form expressions of the bit error ratio (BER) and ergodic sum rate. The impact of an error due to the successive interference cancellation (SIC) is also taken into consideration in the BER analysis. The obtained results with respect to different system parameters are instrumental to provide useful insights into the system performance.